Pengaruh Perputaran Piutang dan Persediaan terhadap Net Profit Margin pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia - Dini Mauliddiarti; Hasbi Assidiki Mauluddi; Hennidah Karnawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The purpose of this research is to know the influence of receivable turnover and inventory turnover on Net Profit Margin (NPM) in the food and beverage companies listed in IDX year 2016-2020. This research uses purposive sampling technique, so that the company sample data obtained are 8 food and beverage companies listed on IDX year 2016-2020. The data used in this research is secondary data obtained from the company financial statements that have been published in IDX. The analytical technique used is multiple linear regression analysis using a tool in the form of IBM SPSS version 25 software. The results of this research indicate that receivable turnover and inventory turnover partially has a negatively and significant effect on NPM, inventory turnover partially has a negatively and significant effect on NPM. Simultaneously account receivable turnover and inventory turnover have a significant influence on NPM.